The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad448
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Behavior Disorders

Abstract: Disruptive behavior is a heterogeneous construct that encompasses a variety of symptoms including tantrums, lying, cheating, noncompliance, theft, and assault. If these symptoms are severe, persistent, and accompanied by impairment in social contexts (e.g., family, peers, school), the individual may meet the criteria for one of the two diagnoses for disruptive behavior disorders (DBDs): oppositional defiant disorder (ODD) and conduct disorder (CD). Although ODD and CD tend to share risk and protective factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…CU traits comprise low empathy, lack of guilt, shallow emotions, and a lack of concern about performance (Frick, Ray, Thornton, & Kahn, 2014). Antisocial children with elevated CU traits show a more severe, aggressive and chronic pattern of antisocial behaviour, unique biological, emotional, social-motivational and cognitive correlates, and reduced responsiveness to intervention compared to antisocial children with low levels of these traits (Allen, Hwang, & Huijding, 2020). The most recent edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; American Psychiatric Association, 2013) therefore introduced CU traits as a specifier for conduct disorder under the label of 'limited prosocial emotions'.…”
mentioning
confidence: 99%
“…CU traits comprise low empathy, lack of guilt, shallow emotions, and a lack of concern about performance (Frick, Ray, Thornton, & Kahn, 2014). Antisocial children with elevated CU traits show a more severe, aggressive and chronic pattern of antisocial behaviour, unique biological, emotional, social-motivational and cognitive correlates, and reduced responsiveness to intervention compared to antisocial children with low levels of these traits (Allen, Hwang, & Huijding, 2020). The most recent edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5; American Psychiatric Association, 2013) therefore introduced CU traits as a specifier for conduct disorder under the label of 'limited prosocial emotions'.…”
mentioning
confidence: 99%
“…The schools who participated in the research had high male:female pupil ratios (School A's student body was comprised of 80% male pupils and for School B it was 87.5%), therefore future work could target schools with a greater number of female pupils. Teachers tend to report poorer quality TCRs with boys (McGrath & Van Bergen, 2015), and boys show more physical aggression towards their classmates and teachers, while girls display more covert antisocial behavior and relational aggression (e.g., ostracism, rumour spreading) (Allen, Hwang, & Huijding, 2020). This suggests that future research should include a mixed gender sample to examine if there are gender differences in pupils' perceptions of RPIs and their impact on TCR quality.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For instance, Gritti et al [ 2 ] found that 8.5% (3.85% borderline, 4.7% clinical) of children suffered from externalizing behavioral problems. These difficulties lead to several adverse outcomes and may represent a significant economic burden for the child, their family, their victims, and, more broadly, for society [ 3 , 4 ], with estimated public costs per child exceeding USD 70,000 over seven years.…”
Section: Introductionmentioning
confidence: 99%